Теоретична модель для ефекту негативної диференціальної провідності у 2D напівпровідникових моношарах - Lytovchenko, V. G.; Kurchak, A. I.; Strikha, M. V. (Publishing house "Academperiodika", 2018)
A simple theoretical model of electron heating in a system with two valleys is applied for the first time to describe 2D semiconductor monolayers of the MoS2 and WS2 types. The model is demonstrated to describe sufficiently well the available experimental data on the negative differential conductance effect in a WS2 monolayer. It confirms a possibility to fabricate Gunn diodes of a new generation based on the structures concerned. Such diodes are capable of generating frequencies of an order of 10 GHz and higher, which makes them attractive for many practical applications.